Manajemen Ekstrakurikuler Peserta Didik di Madrasah Aliyah Negeri 1 Merangin - Darsiah Darsiah (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2021)
Extracurricular activities are activities outside of school hours as a means of channeling students' talents and skills at school. Extracurricular management carried out by MAN 1 Merangin is planning, organizing, implementing, and evaluating, extracurricular activities are included in the annual work plan of the education unit. The efforts of the principal of MAN 1 Merangin to improve extracurricular services, namely in the field of facilities and infrastructure, to support extracurricular activities such as: Providing special rooms, required equipment, and costs required in carrying out these activities and having professional teachers in accordance with their fields. In developing students' talents to achieve school achievement, the principal has a strategy in increasing student talent and carrying out the managerial functions of a leader.